2015
DOI: 10.4049/jimmunol.1403209
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1–CX3CR1 Interaction Increases the Population of Ly6C−CX3CR1hi Macrophages Contributing to Unilateral Ureteral Obstruction–Induced Fibrosis

Abstract: Chemokines modulate inflammatory responses that are prerequisites for kidney injury. The specific role of monocyte-associated CX3CR1 and its cognate ligand CX3CL1 in unilateral ureteral obstruction (UUO)–induced kidney injury remains unclear. In this study, we found that UUO caused a CCR2-dependent increase in numbers of Ly6Chi monocytes both in the blood and kidneys and of Ly6C−CX3CR1+ macrophages in the obstructed kidneys of mice. Using CX3CR1gfp/+ knockin mice, we observed a rapid conversion of infiltrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 48 publications
(51 reference statements)
2
60
0
Order By: Relevance
“…The chemokine fractalkine (CX3CL1) and its CX3CR1 receptor provide another example whereby injured epithelia qualitatively alter the inflammatory infiltrate. The interaction between fractalkine, expressed on injured epithelia, and CX3CR1, expressed on macrophages/DCs, not only directs macrophage recruitment and adhesion, but also increases the survival specifically of pro-fibrotic macrophages (Ly6C − CX3CR1 hi )(81, 82). Thus, injured proximal tubule cells modulate the amount and phenotype of infiltrating macrophages/DCs through production of cytokines.…”
Section: Epithelial Crosstalk With Inflammatory Cellsmentioning
confidence: 99%
“…The chemokine fractalkine (CX3CL1) and its CX3CR1 receptor provide another example whereby injured epithelia qualitatively alter the inflammatory infiltrate. The interaction between fractalkine, expressed on injured epithelia, and CX3CR1, expressed on macrophages/DCs, not only directs macrophage recruitment and adhesion, but also increases the survival specifically of pro-fibrotic macrophages (Ly6C − CX3CR1 hi )(81, 82). Thus, injured proximal tubule cells modulate the amount and phenotype of infiltrating macrophages/DCs through production of cytokines.…”
Section: Epithelial Crosstalk With Inflammatory Cellsmentioning
confidence: 99%
“…15,16 MMP9 activity was inhibited using MMP9 inhibitor or MMP9-neutralizing antibody, which was administered daily for four consecutive days from day 0 to 3 (for early stage of UUO), 6 to 9 (for mid stage) or 10 to 13 (for late stage). 1,10,[21][22][23][24] Therefore, we hypothesized that neutrophil infiltration enhances renal fibrosis by promoting the expansion of inflammation and macrophage accumulation in the obstructed kidney; moreover, neutrophil produces MMP9 in the kidney to promote macrophage infiltration. Many reports demonstrated that inflammatory cells, including neutrophils, produce MMP9 during tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…10,[17][18][19][20] Previous results by us and other researchers also demonstrated that the early stage of UUO is the progression of inflammatory cell infiltration, and a high peak occurred from days 3-7. 1,10,[21][22][23][24] Therefore, we hypothesized that neutrophil infiltration enhances renal fibrosis by promoting the expansion of inflammation and macrophage accumulation in the obstructed kidney; moreover, neutrophil produces MMP9 in the kidney to promote macrophage infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Ly6‐C high inflammatory monocytes respond to inflammatory signals and leave the circulation by extravasation, whereas Ly6‐C low monocytes patrol the luminal side of the vasculature. Recent studies have demonstrated that Ly6‐C high inflammatory monocytes are increased in the tissues in mouse models of fibrosis, including lung fibrosis, unilateral ureteral obstruction–induced fibrosis, and bleomycin‐induced skin fibrosis . Depending on the specific cytokines to which they are exposed, tissue Ly6‐C high macrophages down‐regulate Ly‐6C and polarize cells into tissue‐remodeling/profibrotic (M2‐like) macrophages .…”
Section: Discussionmentioning
confidence: 99%